Phenomenon Rohingyar and The presence of a network of Muslim Myanmar In Nakhon Si Thammarat Province - Tiwatsirikul, Krisana (Asia Social Issues, 2017)
The capture of 102 Rohingyar people in Nakhon Si Thammarat Province has led to the beginning of the presence of diaspora Myanmar Muslims who, for ten years, have lived in a Muslim community. They have a network linking them and have lived in harmony through the shared Islamic faith. Because of this, the Myanmar Muslims have gradually been accepted by people in the community. The diaspora Myanmar Muslims have created a Muslim identity, evoking recognition from the community as well as from Thai Muslims in general. The coordinators who acted as leaders have created networks for negotiation with the local legal authorities. They have an identity recognized by laws, but outside legal boundaries a ‘blurry’ identity. Nevertheless, these coordinators have been able to gain acceptance and expand their powers of negotiation as the “leaders” of the diaspora Myanmar in Nakhon Si Thammarat.